Understanding unfolding and refolding of the antibody fragment (Fab) III: mapping covalent and non-covalent interactions during in-vitro refolding of light chain, heavy chain, and Fab. - Gani, Kayanat; Chirmade, Tejas; Ughade, Santosh; Thulasiram, Hirekodathakallu; Bhambure, Rahul (Biochemical Engineering Journal, 2022)
In-vitro refolding of the antibody fragments from inclusion bodies is a critical manufacturing bottleneck. We have previously reported that Fab refolding involves the formation of an intermediate. To further decode the refolding pathway, we have mapped the covalent and non-covalent interactions during in-vitro refolding of individual light chain (LC), heavy chain (HC), and intact Fab. Intrinsic fluorescence analysis was performed to map the non -covalent interactions, whereas time-dependent disulfide mapping was performed using LC-MS/MS analysis under non-reducing and reducing atmospheres. Refolding of purified LC, HC, and intact Fab (Biosimilar rHu Ranibi-zumab) was investigated in the study. Under the reducing condition, LC, HC, and intact Fab required around 96, 30, and 70 h, respectively, whereas, under non-reducing conditions, they required only 48, 10, and 48 h, respectively, to acquire the native conformation. The disulfide bond mapping revealed that the bond between LC_Cys23/Cys88 is more unstable. The peptides mapped with the inter-chain disulfide bond were identified at 48 h during the refolding and can be considered as the rate-limiting step in (Fab) refolding. We have also studied a new refolding strategy involving assembly of separately refolded LC and HC into Fab molecule. In this case the Fab refolding yield was low (18.0 +/- 1.36%), indicating inefficient assembly of refolded LC and HC chain into native Fab molecule.
Keywords: Antibody fragment; Disulfide bond formation; In-vitro refolding; Light and heavy chain; rHu Ranibizumab

Understanding unfolding and refolding of the antibody fragments (Fab). II. Mapping intra and inter-chain disulfide bonds using mass spectrometry - Nainwal, Neeraj; Chirmade, Tejas; Gani, Kayanat; Rana, Sunil; Bhambure, Rahul (Biochemical Engineering Journal, 2022)
Disulfide bond formation in recombinant protein therapeutics has a significant impact on the integrity and biological activity of the drug product. Formation of the disulfide linkage is the key rate-limiting step in in vitro refolding and overall manufacturing of the antibody fragments (Fab). This investigation is focused on mapping the intra, and inter-chain disulfide bonds in the in vitro refolded antibody fragments by using mass spectrometry (MS). Biosimilar rHu Ranibizumab and rHu Certolizumab expressed using E. coli were selected for the study. Both Fabs contain ten cysteine residues leading to two intra-chain disulfide bonds on each subunit and a single interchain disulfide linkage. rHu Certolizumab has an additional cysteine which is unpaired and used for pegylation. The amino acid sequence in the disulfide-bonded peptides was confirmed by Collision-induced dissociation (CID), Electron transfer dissociation (ETD) and High-energy collision dissociation (HCD). The light chain (LC) intra-chain disulfide is formed between Cys23-Cys88 and Cys134-Cys194 in both the Fabs. The heavy chain (HC) intra-chain disulfides are formed between Cys22-Cys96 and Cys150-Cys206 in rHu Ranibizumab. LC and HC subunits of rHu Ranibizumab are covalently linked by disulfide linkage formed between Cys214 of LC and Cys226 of HC. This study suggests that information from multiple MS platforms and orthogonal methods for peptide fragmentation can be effectively used to map disulfide linkages in biosimilar therapeutic proteins.
Keywords: Antibody fragments (Fab); Collision-induced dissociation; Electron transfer dissociation; High-energy collision dissociation; in vitro refolding; Ranibizumab